Population Genetics Reveals Invasion Origin of Coilia brachygnathus in the Three Gorges Reservoir of the Yangtze River, China - Zhai, Dongdong; Li, Bo; Xiong, Fei; Jiang, Wei; Liu, Hongyan; Luo, Chenhao; Duan, Xinbin; Chen, Daqing (Frontiers in Ecology and Evolution, 2022)
Non-indigenous fish invasions have posed a serious threat to global fish diversity and aquatic ecosystem security. Studying the invasion sources, pathways, and genetic mechanisms by means of population genetics is helpful in the management and control of non-indigenous fishes. In this study, we used mitochondrial Cyt b gene, D-Loop region and microsatellite markers to analyze the genetic diversity and population structure of 12 Coilia brachygnathus populations from the native and invaded regions of the Yangtze River Basin in order to explore the invasion sources, pathways, and genetic mechanisms of C. brachygnathus in the Three Gorges Reservoir. The results showed that the main invasion sources of C. brachygnathus in the Three Gorges Reservoir were the Poyanghu Lake, Dongtinghu Lake, Changhu Lake, and other populations in the middle reaches of the Yangtze River. The invasion pathway may have involved moving upstream through the operation of ship locks. The genetic diversity of C. brachygnathus in the invasive populations was significantly smaller than in the native populations, indicating a founder effect. The low genetic diversity did not affect the successful invasion, confirming that genetic diversity and successful invasion do not always have a simple causal relationship. These results can provide basic data for the prevention and control of C. brachygnathus in the Three Gorges Reservoir and study case for understanding the mechanism of invasion genetics.